2001
DOI: 10.1128/aac.45.2.627-629.2001
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Surveillance of Antibiotic Resistance in Streptococcus pneumoniae in Four African Cities

Abstract: Worldwide spread of antibiotic resistance in Streptococcus pneumoniae is a major problem. However, data from West and North African countries are scarce. To study the level of resistance and compare the situations in different cities, a prospective study was conducted in Abidjan (Ivory Coast), Casablanca (Morocco), Dakar (Senegal), and Tunis (Tunisia), from 1996 to 1997. The resistances to eight antibiotics of 375 isolates were studied by E test, and the results were interpreted using the breakpoints recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
3
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 29 publications
2
21
3
3
Order By: Relevance
“…In the USA since 1983, the prevalence of ß-lactamase producing H. influenzae rose from 14.5% to 37.5% in 1997, providing resistance to penicillin and first generation cephalosporins (10). In our study only 8.6% of H. influenzae produced ß-lactamase although these were not characterised further.…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…In the USA since 1983, the prevalence of ß-lactamase producing H. influenzae rose from 14.5% to 37.5% in 1997, providing resistance to penicillin and first generation cephalosporins (10). In our study only 8.6% of H. influenzae produced ß-lactamase although these were not characterised further.…”
Section: Discussioncontrasting
confidence: 40%
“…These two drugs are among the most commonly available in most public hospitals for treatment of acute respiratory tract infections and other bacterial infections, and the high level of resistance would render them less effective for treatment of these infections. As in other studies from African countries (8,10,17) pneumococcal isolates from our study were susceptible to semi-synthetic penicillins and extended spectrum cephalosporins, but these drugs may be unavailable or are too expensive to be afforded by most patients who seek care at public hospitals in Kenya.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Penicillin G resistance in S. pneumoniae infection was observed in Africa as well as in other countries (1,6). In our study, high resistance rate (31.3%) of S. pneumoniae to penicillin G was observed, which is similar to data previously reported in a study conducted by Gueye and al.…”
Section: Articlesupporting
confidence: 82%
“…Spain, Hungary, and South Africa have the highest rates in the world (6,7,16). In this study, rates of co-trimoxazole resistance are relatively low compared to those found in African and Asian countries (3,9,11,25). This may be explained by the fact that antibiotics are not delivered without prescription and that co-trimoxazole is used as the second line of defense in treating bacterial acute lower respiratory tract infections after amoxicillin failure.…”
Section: Vol 47 2003mentioning
confidence: 84%